2021
DOI: 10.1093/hmg/ddab129
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of somatic CAG repeat expansion with striatal neurodegeneration in HD knock-in animal models

Abstract: Our previous work has established a huntingtin knock-in (KI) pig model that displays striatal neuronal loss, allowing us to examine if somatic CAG expansion in striatum accounts for the preferential neurodegeneration in Huntington disease (HD). We found that HD KI pigs do not display somatic CAG expansion in striatum as HD KI mice and that the majority of polyQ repeats in exon 1 HTT in the striatum of HD KI mice are fairly stable. We also found that striatal MSH2 and MLH3, which are involved in DNA repair, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Also, immunostaining with the antibody to Iba-1 revealed a marked increase of the microglial cells in KI pig brain, which is more abundant in the striatum than in the cortex. Quantification of the number of different types of cells revealed that the KI striatum had the most severe loss of NeuN-positive cells and the highest increase in glial cell numbers, which was not observed in the age-matched HD KI mouse ( 66 , 67 ). Additionally, Valekova et al.…”
Section: Neuroinflammation In Different Animal Models Of Huntington’s...mentioning
confidence: 84%
See 1 more Smart Citation
“…Also, immunostaining with the antibody to Iba-1 revealed a marked increase of the microglial cells in KI pig brain, which is more abundant in the striatum than in the cortex. Quantification of the number of different types of cells revealed that the KI striatum had the most severe loss of NeuN-positive cells and the highest increase in glial cell numbers, which was not observed in the age-matched HD KI mouse ( 66 , 67 ). Additionally, Valekova et al.…”
Section: Neuroinflammation In Different Animal Models Of Huntington’s...mentioning
confidence: 84%
“…Also, immunostaining with the antibody to Iba-1 revealed a marked increase of the microglial cells in KI pig brain, which is more abundant in the striatum than in the cortex. Quantification of the number of different types of cells revealed that the KI striatum had the most severe loss of NeuN-positive cells and the highest increase in glial cell numbers, which was not observed in the age-matched HD KI mouse (66,67). Additionally, Valekova et al used transgenic HD minipig, which was generated by injecting lentiviral vectors carrying truncated mutant huntingtin genes that encode 124 glutamine repeats integrated into chromosome 1q24-q25 and transmitted through successive three generations (68), for investigating multiple cytokines (69).…”
Section: Large Animal Modelsmentioning
confidence: 87%
“…One of the well-documented events in HD mice is the somatic CAG repeat instability in the striatum, a brain region that is preferentially affected in HD (Swami et al, 2009 ). Further investigation of CAG repeat lengths in various brain regions of HD KI pigs showed that the CAG repeats are fairly stable in the striatum (Bai et al, 2021 ). These findings point to the potential regulation of the somatic instability of CAG repeats by species-dependent factors and stress the role of polyglutamine toxicity rather than CAG instability in large animals.…”
Section: New Insights From Large Animal Models Into Disease Mechanismsmentioning
confidence: 99%
“…Although direct comparison of HD patient and animal model data is difficult due to differences in lifespan, mouse models of HD appear to require very long repeat lengths relative to humans to achieve the frequency and size of mutations that is seen in humans [51][52][53]. Additionally, a knock-in minipig model with CAG150 shows less instability than a knock-in mouse with comparable age and repeat length [54]. The mechanism for the species difference is not fully understood but likely involves DNA repair proteins that influence instability [43,49].…”
mentioning
confidence: 99%